Effect of Varying Levels of Fibrolytic Enzymes Supplementation on Digestibility of Nutrients and Plane of Nutrition in Gir Calves - Kadam, Sandip J; Garg, Deendayal; Savsani, Harish H; Patel, Sneh D; Patbandha, Tapas K; Karangiya, Vijay K; Sanchaniya, Jatin M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to investigate the effect of fibrolytic enzyme on digestibility of nutrients and plane of nutrition in Gir  calves. Fifteen male Gir calves of around one year age were randomly divided into three groups with five calves in each and experiment  was conducted for 90 days. Three TMR (total mixed ration, roughage: concentrate ratio 60:40) treatments used were: only TMR (T1), TMR  supplemented with exogenous fibrolytic enzymes (EFEs, cellulase 10,00,000 IU/g and xylanase 1,50,000 IU/g in 1:1 ratio), at 0.025% of  DM (T2) and at 0.050% of DM (T3). Digestibility (%) of dry matter (66.77 vs. 61.95), organic matter (70.18 vs. 66.58) and cellulose (58.54 vs.  53.40) were significantly (p
Keywords: Digestibility; Exogenous Fibrolytic enzymes; Gir calves; Nutrient intake